Evaluation of barley protein concentrate and fish protein concentrate, made from trimmings, as sustainable ingredients in Atlantic salmon (Salmo salar L.) feeds. (10th November 2014) - Bell, J.G.; Strachan, F.; Roy, W.J.; Matthew, C.; McDonald, P.; Barrows, F.T.; Sprague, M.
Abstract: Barley protein concentrate (BPC) was tested as a protein source in the diets of Atlantic salmon post‐smolts. Fish were fed one of four experimental diets consisting of a fish meal/soya protein concentrate control (CT) along with two feeds supplemented with increasing levels of BPC replacing the more costly SPC. A fourth diet partially replaced FM in the high BPC diet with a liquid fish protein concentrate (FPC) made from fish trimmings. No significant differences were observed in terms of growth at the end of the 12‐week feeding period, although the protein efficiency ratio (g gain g −1 protein consumed) was significantly lower for the control compared to fish fed diets containing either BPC only or FPC and BPC. This suggests that diets containing BPC had a beneficial effect when compared to the control diet. Furthermore, the lack of any detriment to fish growth in diets containing BPC suggests there are no significant issues regarding any negative effects of potential antinutritional factors which can otherwise be the case with other plant origin products. The data presented in this study indicate that BPC and FPC are products which could be of benefit to salmon culture, and related species, in providing a valuable new raw material to the industry.